2021
DOI: 10.1111/1541-4337.12770
|View full text |Cite
|
Sign up to set email alerts
|

Thermal treatment of common beans (Phaseolus vulgaris L.): Factors determining cooking time and its consequences for sensory and nutritional quality

Abstract: Over the past years, the shift toward plant‐based foods has largely increased the global awareness of the nutritional importance of legumes (common beans (Phaseolus vulgaris L.) in particular) and their potential role in sustainable food systems. Nevertheless, the many benefits of bean consumption may not be realized in large parts of the world, since long cooking time (lack of convenience) limits their utilization. This review focuses on the current insights in the cooking behavior (cookability) of common bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 220 publications
(303 reference statements)
1
31
0
3
Order By: Relevance
“…The longer cooking times and an increase in energy consumption are deterrent attributes contributing to low utilization of beans at household level ( Wood, 2017 ; Cichy et al., 2015 ; Siqueira et al., 2013 ; Rehfuess, 2006 ). Cooking time is a function of heritable traits, environmental, and storage conditions, as well as pre-cooking and cooking treatments ( Wainaina et al., 2021 ; Wood, 2017 ). Previous studies done by other authors have reported that starch composition (amylose and amylopectin ratio) and protein content affect cooking time ( Chigwedere et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The longer cooking times and an increase in energy consumption are deterrent attributes contributing to low utilization of beans at household level ( Wood, 2017 ; Cichy et al., 2015 ; Siqueira et al., 2013 ; Rehfuess, 2006 ). Cooking time is a function of heritable traits, environmental, and storage conditions, as well as pre-cooking and cooking treatments ( Wainaina et al., 2021 ; Wood, 2017 ). Previous studies done by other authors have reported that starch composition (amylose and amylopectin ratio) and protein content affect cooking time ( Chigwedere et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 200 g of each bean were soaked, in each of the four different types of water, for precisely 12 h. This procedure was replicated three times ( n = 3). Soaking beans in water for at least 12 h before cooking has been previously recommended ( Wainaina et al., 2021 ; Abdel-Hameed and Latif, 2019 ). From the eight bean varieties, 200 g of the right bean variety was soaked in the right type of water until all samples, as per schedule for the respective day of cooking, were completed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventionally, harvested beans are stored for prolonged periods due to their excellent shelf life and to ensure availability during the off-season. Consequently, the beans are dried to achieve a moisture content that is biologically and chemically safe for long-term storage [ 13 , 14 ]. During cooking, the time to achieve cell separation and softening is considerably longer in beans with the HTC defect than in regular beans [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%